Phenotypic and molecular characterization of Acinetobacter baumannii isolates causing lower respiratory infections among ICU patients. (March 2019) - Jain, Manisha; Sharma, Amit; Sen, M.K.; Rani, Vandana; Gaind, Rajni; Suri, J.C.
Abstract: Background: Multi-drug resistant Acinetobacter baumannii has emerged as important nosocomial pathogen associated with various infections including lower respiratory tract. Limited therapeutic options contribute to increased morbidity and mortality. Acinetobacter baumannii has the ability to persist in the environment for prolonged periods. Breach in infection control practices increases the chances of cross transmission between patients and inter/intraspecies transmission of resistance elements. The present prospective work was conducted among patients with lower respiratory tract infections (LRTI) in the intensive care unit (ICU) to study the etiology with special reference to Acinetobacter baumannii and the role of immediate patient environment in the ICU as possible source of infection. Acinetobacter baumannii were characterized for antimicrobial susceptibility, mechanism of carbapenem resistance and virulence determinants. Molecular typing of the clinical and environmental isolates was undertaken to study the probable modes of transmission. Materials and methods: Appropriate respiratory samples from 107 patients with LRTI admitted to ICU during September 2016 to March 2017 were studied for likely bacterial pathogens. Environmental samples (n = 71) were also screened. All the samples were processed using conventional microbiological methods. Consecutive Acinetobacter spp. isolated from clinical and environmental (health care workers and environment from ICU) samples were included in the study. Antimicrobial susceptibility was performed as per CLSI guidelines. Carbapenem resistance, mediated by carbapenemase genes ( bla OXA-23-like, bla OXA-24-like, bla OXA-58-like and bla NDM-1 ) were studied by PCR. Biofilm forming ability was tested phenotypically using microtitre plate method. Pulse Field Gel Electrophoresis (PFGE) was used to study clonality of the clinical and environmental isolates. Results: The prevalence of Acinetobacter baumannii was 26.2% (28/107) and 11.26% (8/71) among patients with LRTI and environmental samples respectively. The carbapenem resistance was high, 96.42% (27/28) and 87.5% (7/8) in clinical and environmental isolates respectively. The most common carbapenemase associated with resistance was bla OXA-23-like gene followed by bla NDM-1 among both the clinical and environmental isolates. All isolates were sensitive to colistin (MIC ≤ 1 μg/ml). Biofilm production was observed among all clinical (n = 28) and 87.5% (7/8) of the environmental isolates. Line listing of the cases suggests the occurrence of infections throughout the study period with no significant clustering. On PFGE, 12 clusters were observed and 16/36 isolates were present in one single cluster that included both clinical and environmental isolates which were either carbapenem resistant or sensitive. Discussion: Carbapenem resistant Acinetobacter baumannii (CRAB) is an important cause of LRTI in the ICU. PFGE suggests spread of carbapenem resistant isolates via cross transmission among patients and the environment. The detection of bla NDM-1 gene among Acinetobacter baumannii and existence of carbapenem resistant and sensitive isolates within the same clones suggests horizontal transmission of resistant genes among various bacterial species. The ability of Acinetobacter baumannii to form biofilms may contribute to its persistence in the environment. This along with breach in infection control practices are the likely factors contributing to this transmission. This information can be used to strengthen and monitor infection control (IC) and the hospital cleaning and disinfection practices to prevent spread of resistant organisms within the ICU. Colistin remains drug of choice for management of CRAB.